2010
DOI: 10.1007/s00024-010-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic Slip from the 6 October 2008, M w6.3 Damxung Earthquake, Tibetan Plateau, Constrained by InSAR Observations

Abstract: Coseismic deformation fields of the 6 October 2008 M w 6.3 Damxung earthquake were obtained from interferometric synthetic aperture radar by using three descending and two ascending Envisat images. Significant coseismic surface deformation occurred within 20 km 9 20 km of the epicenter with a maximum displacement of *0.3 m along the satellite line of sight. We model a linear elastic dislocation in a homogeneous half space and use a nonlinear constraint optimized algorithm to estimate the fault location, geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The InSAR method has become a widely used technique for extracting the deformation of the earth’s surface resulting from an earthquake event [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In this study, to map the 28 August 2009 Dachaidan Mw 6.3 earthquake displacement field, SAR images were acquired before and after the event by the Envisat satellite, which operates at C-band wavelengths ( i.e.…”
Section: Insar Data Processing and Coseismic Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The InSAR method has become a widely used technique for extracting the deformation of the earth’s surface resulting from an earthquake event [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In this study, to map the 28 August 2009 Dachaidan Mw 6.3 earthquake displacement field, SAR images were acquired before and after the event by the Envisat satellite, which operates at C-band wavelengths ( i.e.…”
Section: Insar Data Processing and Coseismic Deformationmentioning
confidence: 99%
“…Recently, geodetic techniques have been employed for accurate monitoring of the surface deformation related to the earthquake fault [ 7 ]. The Interferometric Synthetic Aperture Radar (InSAR), a kind of geodetic measurement technique that does not require any ground control point, has frequently been utilized for analyzing the process, development, and occurrence of an earthquake in detail [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that high-precision and high-spatial resolution co-seismic displacement from geodetic techniques, such as Interferometric Synthetic Aperture Radar (InSAR) and Global Positioning System (GPS) methods, is critical for understanding the static co-seismic rupturing mechanism of the underground fault regime [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In addition, post-seismic studies of tens of strong and large (≥Mw 6) earthquakes around the world indicated that post-seismic deformation can play an important role in a detailed determination of the post-seismic response to an earthquake and the accurate assessment of the future seismic risk [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…These along strike and downdip extents are clearly less, by 10 and 5 km, respectively, than those outlined by the aftershocks. The slip averaged over this region is no larger than 0.6 m, yielding a mean static stress drop of 3–4MPa, which is comparable to the recent thrust‐slip Pishan earthquake ( Mw 6.4) in the western Kunlun Shan and normal‐faulting Dangxiong earthquake ( Mw 6.3) in south Tibet (He et al, ; Qiao et al, ). The stress drops of the intraplate earthquake, shown here to be approximately 4 MPa averaged over three moderate magnitude events with different mechanisms.…”
Section: Discussionmentioning
confidence: 64%